Remittances, Poverty Reduction and Inclusive Growth in the Resource-Poor Former Soviet Union Countries - Sarvar Gurbanov; Vusal Mammadrzayev; Hasan Isgandar (Economics, Law, and Institutions in Asia Pacific, 2021)
Estimations show that approximately US 23 billion is required for Georgia to meet its climate and environmental targets up to 2030. As the current Nationally Determined Contribution reveals, considering 1990 as a base year, the Republic of Georgia plans a 35% decrease in greenhouse gas emissions by 2030. If the country has financial and technical support, commitment to limit emissions may rise as high as 50%–57%. As part of the Paris Climate accord, developed nations pledged to channel US 100 billion toward low-income countries between 2020 and 2025. Recent estimates by the OECD show that developed nations will be able to reach their US 100 billion pledge only in 2023. Considering this lag for many developing countries, including Georgia, mobilizing private finance via green digital finance will be vital. The policymakers of the Republic of Georgia are very ambitious about adopting green digital finance solutions. This initiative has potential to fill the gap in public funding sources. Hence, this study analyzes the potential for private sector financing through the digitization of green finance. The current study illustrates the extent to which green finance and its digitization level are available in the Republic of Georgia. The major policy implication is that the country faces unintended consequences even though there is a robust regulatory attempt to mobilize private financial sources. This case study is relevant for many developing countries for drawing lessons on better policymaking.
Keywords: G20; G23; 330; green digital finance; regulatory sandbox